Differentiating Moebius syndrome and other congenital facial weakness disorders with electrodiagnostic studies. Issue 4 (19th January 2021) - Lehky, Tanya; Joseph, Reversa; Toro, Camilo; Wu, Tianxia; Van Ryzin, Carol; Gropman, Andrea; Facio, Flavia M.; Webb, Bryn D.; Jabs, Ethylin W.; Barry, Brenda S.; Engle, Elizabeth C.; Collins, Francis S.; et al.
Abstract: Introduction: Congenital facial weakness (CFW) can result from facial nerve paresis with or without other cranial nerve and systemic involvement, or generalized neuropathic and myopathic disorders. Moebius syndrome is one type of CFW. In this study we explored the utility of electrodiagnostic studies (EDx) in the evaluation of individuals with CFW. Methods: Forty‐three subjects enrolled prospectively into a dedicated clinical protocol and had EDx evaluations, including blink reflex and facial and peripheral nerve conduction studies, with optional needle electromyography. Results: MBS and hereditary congenital facial paresis (HCFP) subjects had low‐amplitude cranial nerve 7 responses without other neuropathic or myopathic findings. Carriers of specific pathogenic variants in TUBB3 had, in addition, a generalized sensorimotor axonal polyneuropathy with demyelinating features. Myopathic findings were detected in individuals with Carey‐Fineman‐Ziter syndrome, myotonic dystrophy, other undefined myopathies, or CFW with arthrogryposis, ophthalmoplegia, and other system involvement. Discussion: EDx in CFW subjects can assist in characterizing the underlying pathogenesis, as well as guide diagnosis and genetic counseling. Abstract : Subjects with congenital facial weakness affecting cranial nerve III, VI, upper face VII, lower face VII, and combined lower face VII and XII (top to bottom) adjacent to illustration of cranial nerves III, IV, VI, and VII. Cover illustration credited to Darryl Leja. For details see Lehky et al. Differentiating Moebius Syndrome and Other Congenital Facial Weakness Disorders with Electrodiagnostic Studies.